Chapter 12. Use of asparagus waste to fortify bakery products - Priss, Olesia; Прісс, Олеся Петрівна; Kostetska, Kateryna; Bulhakov, Pavlo; Булгаков, Павло Олександрович (Scientific Route Tallinn Estonia, 2025)
EN: The modern industry of food production faces constant challenges, raised by growth of population, global environmental changes and high impact of geopolitical factors on the food supply chains. Sustainability in processes of food production and distribution is crucial for food security and rational management of valuable natural resources. High losses, especially in perishable crops like asparagus (up to 50% of the total production), are serious issue, which demands development of new approaches to reduce and rationally utilize the waste. Asparagus is a highly valuable and popular vegetable crop. However, it rapidly loses its commercial quality due to the high level of metabolism in the spears, which contributes to significant product losses during processing and storage. Up to 20% of spears are additionally wasted due to the trimming during the storage, which con tributes significantly to the production losses. The chapter of the monograph is dedicated to the possibility of utilization of waste from asparagus processing for enriching food products, namely bakery products. The basal parts of asparagus spears, which are usually utilized, were proven to con tain high amount of the phenolic compounds. The elemental analysis of the freeze dried asparagus powder showed presence of many valuable microelements and high quantities of protein, which make such powder a valuable dietary supplement. A series of bread recipes in which part of the flour was replaced with the obtained asparagus powder was tested to produce bakery products with enhanced biologi cal value. Four types of low-carbohydrate flours were tested (whole-grain spelt and quinoa, flaxseed, and amaranth), to which asparagus powder was added in various proportions. The bread produced using these new recipes was evaluated based on its physicochemical characteristics and organoleptic properties. It was shown that adding asparagus powder (5–10%) to amaranth, quinoa and flaxseed flour helped retain the shape of produced bread, reduced crumb moisture and facilitated uniform porosity, though did not provide positive impact on the organoleptic properties. At the same time, bread made with whole-grain spelt flour and up to 10% replace ment with asparagus powder met all requirements for each of the indicators. These experimental results thus justify the replacement of up to 10% of spelt flour with asparagus powder to enhance the nutritional value of the product. The use of asparagus powder in the bakery, therefore, allows for the reduction of food waste, the enhancement of product nutritional value through the inclusion of micronutrients, proteins, and antioxidants, and the expansion of the range of bak ery products, including options for consumers with low-carbohydrate or gluten-free dietary needs. /// UA: Сучасна індустрія виробництва продуктів харчування стикається з постійними викликами, які виникають у зв'язку зі зростанням населення, глобальними екологічними змінами та високим впливом геополітичних факторів на ланцюги постачання продовольства. Сталість у процесах виробництва та розподілу продуктів харчування має вирішальне значення для продовольчої безпеки та раціонального управління цінними природними ресурсами. Високі втрати, особливо в швидкопсувних культурах, таких як спаржа (до 50 % від загального обсягу виробництва), є серйозною проблемою, яка вимагає розробки нових підходів до зменшення та раціонального використання відходів.Спаржа є дуже цінною і популярною овочевою культурою. Однак він швидко втрачає свої товарні якості через високий рівень метаболізму в списах, що сприяє значним втратам продукту при переробці та зберіганні. До 20 % списів додатково витрачається через обрізки під час зберігання, що значно сприяє виробничим втратам.Розділ монографії присвячений можливості утилізації відходів переробки спаржі для збагачення харчових продуктів, а саме хлібобулочних виробів. Доведено, що базальні частини спаржі, які зазвичай використовуються, містять велику кількість фенольних сполук. Елементний аналіз порошку ліофілізованої спаржі показав наявність багатьох цінних мікроелементів і велику кількість білка, які роблять такий порошок цінною харчовою добавкою. Серія рецептів хліба, в яких частина борошна замінювалася отриманим порошком спаржі, була випробувана для отримання хлібобулочних виробів з підвищеною біологічною цінністю. Були протестовані чотири види борошна з низьким вмістом вуглеводів (цільнозернова спельта і кіноа, лляне насіння і амарант), в які в різних пропорціях додавали порошок спаржі. Хліб, виготовлений за цими новими рецептурами, оцінювався на основі його фізико-хімічних характеристик та органолептичних властивостей. Показано, що додавання порошку спаржі (5–10 %) до борошна з амаранту, кіноа та льону сприяло збереженню форми виробленого хліба, знижувало вологість м'якушки та сприяло рівномірній пористості, хоча й не давало позитивного впливу на органолептичні властивості. При цьому хліб з цільнозернового борошна зі спельти та заміною до 10 % порошком зі спаржі відповідав усім вимогам за кожним із показників. Таким чином, ці експериментальні результати виправдовують заміну до 10 % борошна зі спельти порошком спаржі для підвищення харчової цінності продукту. Таким чином, використання порошку спаржі в хлібобулочних виробах дозволяє зменшити харчові відходи, підвищити харчову цінність продукту за рахунок включення мікроелементів, білків і антиоксидантів, а також розширити асортимент хлібобулочних виробів, включаючи варіанти для споживачів з низьковуглеводними або безглютеновими дієтичними потребами.
Розділ 12. Використання відходів спаржі для збагачення хлібобулочних виробів
Keywords: asparagus; storage waste; vegetable powder; bread; food product enrichment; спаржа; відходи зберігання; рослинний порошок; хліб; збагачення харчових продуктів